AhR activation underlies the CYP1A autoinduction by A-998679 in rats - Liguori, Michael J.; Lee, Chih-Hung; Liu, Hong; Ciurlionis, Rita; Ditewig, Amy C.; Doktor, Stella; Andracki, Mark E.; Gagne, Gerard D.; Waring, Jeffrey F.; Marsh, Kennan C.; Gopalakrishnan, Murali; Blomme, Eric A.; et al. (Frontiers in Genetics, 2012)
Xenobiotic-mediated induction of cytochrome P450 (CYP) drug metabolizing enzymes (DMEs) is frequently encountered in drug discovery and can influence disposition, pharmacokinetic, and toxicity profiles. The CYP1A subfamily of DMEs plays a central role in the biotransformation of several drugs and environmental chemicals. Autoinduction of drugs through CYP3A enzymes is a common mechanism for their enhanced clearance. However, autoinduction via CYP1A is encountered less frequently. In this report, an experimental compound, A-998679 (3-(5-pyridin-3-yl-1,2,4-oxadiazol-3-yl) benzonitrile), was shown to enhance its own clearance via induction of CYP1A1 and CYP1A2. Rats were dosed for 5 days with 30, 100, and 200 mg/kg/day A-998679. During the dosing period, the compound’s plasma AUC decreased at 30 mg/kg (95%) and 100 mg/kg (80%). Gene expression analysis and immunohistochemistry of the livers showed a large increase in the mRNA and protein levels of CYP1A, which was involved in the biotransformation of A-998679. Induction of CYP1A was confirmed in primary rat, human, and dog hepatocytes. The compound also weakly inhibited CYP1A2 in human liver microsomes. A-998679 activated the aryl hydrocarbon receptor (AhR) in a luciferase gene reporter assay in HepG2 cells, upregulated expression of genes associated with AhR activation in rat liver, and enhanced nuclear migration of AhR in HepG2 cells. Collectively these results demonstrate that A-998679 is an AhR activator that induces CYP1A1 and CYP1A2 expression, resulting in an autoinduction phenomenon. The unique properties of A-998679, along with its novel structure distinct from classical polycyclic aromatic hydrocarbons, may warrant its further evaluation as a tool compound for use in studies involving AhR biology and CYP1A related mechanisms of drug metabolism and toxicity.